Sex Work, Health, and Human Rights 2021
DOI: 10.1007/978-3-030-64171-9_11
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices and Challenges to Sex Worker Community Empowerment and Mobilisation Strategies to Promote Health and Human Rights

Abstract: Sex workers face a number of health and human rights challenges including heightened risk for HIV infection and suboptimal care and treatment outcomes, institutional and interpersonal violence, labour rights violations, and financial insecurity. In response, sex worker-led groups have been formed and sustained across geographic settings to address these challenges and other needs. Over the last several decades, a growing body of literature has shown that community empowerment approaches among sex workers are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…These findings add to a growing body of evidence regarding the importance of community empowerment interventions in facilitating access to HIV/STI prevention among sex workers globally [ 21 , 23 , 35 ]. A global systematic review showed community empowerment interventions to be associated with reductions in HIV (odds ratio [OR]: 0.68; 95% confidence interval [CI]: 0.52–0.89), gonorrhea (OR: 0.61; 95% CI: 0.46, 0.82), chlamydia (OR: 0.74; 95% CI: 0.57, 0.98), and high-titre syphilis (OR: 0.53; 95% CI: 0.41, 0.69) and increased consistent condom use with clients (OR: 3.27; 95% CI: 2.32, 4.62) [ 21 ].…”
Section: Discussionmentioning
confidence: 64%
“…These findings add to a growing body of evidence regarding the importance of community empowerment interventions in facilitating access to HIV/STI prevention among sex workers globally [ 21 , 23 , 35 ]. A global systematic review showed community empowerment interventions to be associated with reductions in HIV (odds ratio [OR]: 0.68; 95% confidence interval [CI]: 0.52–0.89), gonorrhea (OR: 0.61; 95% CI: 0.46, 0.82), chlamydia (OR: 0.74; 95% CI: 0.57, 0.98), and high-titre syphilis (OR: 0.53; 95% CI: 0.41, 0.69) and increased consistent condom use with clients (OR: 3.27; 95% CI: 2.32, 4.62) [ 21 ].…”
Section: Discussionmentioning
confidence: 64%
“…Meanwhile, most of the studies that investigate sex work, are focused on the prevalence of sexually transmitted infections (STIs) among sex workers and the measures taken to prevent their spread (for, e.g., see Steen and Dallabetta, 2003 ; Argento et al, 2019 ; Platteau et al, 2022 ); the issue of sex trafficking, examining its causes, effects, and potential solutions (for, e.g., see Gerassi et al, 2021 ; Cockbain et al, 2022 ; Motseki and Mofokeng, 2022 ); sexual abuse and exploitation in the sex industry, including the use of violence, coercion, and human rights violations (for, e.g., see UN Women, 2020 ; Navarrete Gil et al, 2021 ), also well-being of sex workers, including their physical and mental health ( Romans et al, 2001 ; Beattie et al, 2020 ; Armstrong, 2021 ), as well as their economic and social status, and legal and policy issues governing sex work, examining their effectiveness in protecting the rights of sex workers and preventing exploitation (for, e.g., see Graham, 2017 ; Platt et al, 2018 ). However, little is known about sex workers’ motivation to engage in sex.…”
Section: Introductionmentioning
confidence: 99%
“…Many have experienced homelessness (Macon & Tai, 2022), incarceration (Socías et al, 2015), mental illness (Beattie et al, 2020), neglect or abuse (Benoit et al, 2015); intimate partner violence (Hong et al, 2022), workplace violence (Deering et al, 2014) or substance use (Iversen et al, 2021). There is also a disproportionate burden of HIV within the sex worker community (Paz-Bailey et al, 2016), potentially related to economic vulnerabilities which affect sex workers' ability to negotiate condom use (Gil et al, 2021). Additionally, the criminalization of sex work, police harassment, perceived stigma surrounding sex work and systemic racism are all reported to be structural barriers impeding sex workers' access to health care (Goldenberg et al, 2022;Potter et al, 2022).…”
Section: Introductionmentioning
confidence: 99%